PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMUNIKASI DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PEGAWAI (STUDI PADA LPMP PROVINSI JAWA TENGAH) - Ulfa Noviana, 1252020029; Rijanti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2014)
Performance of employees in LPMP Central Java is still not optimal characterized by the presence of mentoring activities that should be carried out in each district / city in Central Java in order to provide guidance to units and educational programs in the form of quality assurance activities in the unit and education programs that do not satisfy standard targets. This study used purposive sampling technique is to take a sample with PNS criteria and service life of more than 3 years with a minimum education D3 123 people. Test instruments performed using factor analysis is to test the validity and test reliablilitas. Analysis using multiple linear regression models using the coefficient of determination test and F-test and t-test as a test of the hypothesis. The results of this research note that the quality of work life obtain any significant positive effect of job satisfaction, communication significant positive effect on job satisfaction, quality of work life significant positive effect on organizational commitment, communication significant positive effect on organizational commitment, job satisfaction was not significant positive effect on organizational commitment, quality of work life is not significant positive effect on performance, communication significant positive effect on performance, job satisfaction significant negative effect on performance, organizational commitment significant positive effect on performance, job satisfaction does not mediate the performance quality of work life, job satisfaction does not mediate the communication performance, organizational commitment mediates the performance quality of work life, organizational commitment did not mediate the communication on the performance, the most dominant variable affecting the job satisfaction is communication, the most dominant variables influence organizational commitment is communication while the most dominant variable affecting the performance is the organizational commitment. Keywords: quality of work life, communication, job satisfaction, organizational commitment, performance